ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP SUKUK KORPORASI DI INDONESIA TAHUN 2014-2021 - Pratama, Mohammad Daffa; Pimada, Laila Masruro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Corporate sukuk is an alternative instrument for companies to obtain financing with a safer level of risk. However, when compared to other Islamic capital market products, the number of corporate sukuk products is the least and has not dominated the Islamic capital market. Good macroeconomic conditions can reflect the investment climate and affect the company's growth sukuk issued by issuers. This study aims to determine the effect of macroeconomic variables, namely economic growth, inflation, and exchange rates on corporate sukuk in Indonesia. This study uses 93 samples of data on economic growth, inflation, and exchange rates taken in the period January 2014-December 2021. This study uses two methods, namely quantitative methods and descriptive analysis methods. The quantitative method used to test this research is to use the model used for vector autoregressive (VAR). However, if the variables used in this study pass the stationary test at first difference and there is cointegration, then the quantitative method of Vector Error Correction Model (VECM) is used. The results of this study indicate that the inflation variable affects corporate sukuk in the short and long term in a negative direction. Meanwhile, the variables of economic growth and exchange rate do not affect corporate sukuk in the short term but affect corporate sukuk in the long term.